Information support for the procedure of measuring the flow rate of water in open channels by a water current meter with Arduino Micro board - Reut, Dmytro Tagirovych; Klimov, Serhii; Klimova, Anastasiya (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2020)
The modernization of a typical water current meter is proposed to facilitate hydrological observations on natural and artificial open watercourses. An Arduino Pro Micro microcontroller board was used to read the speed of the current meter and primary data processing, programs were developed: for the lower level - a microcontroller located on the board, and for the upper level - a smartphone to determine the water speed. The programs take into account the peculiarities of converting data on the flow rate of water with a current meter and allow you to enter additional indicators that reduce the uncertainty of the results.